Uncertainty as a Factor in Investment Decisions : The Case of the Russian Federation's Regions - Levina, Irina A.; Kisunko, Gregory V.; Marques, Israel I.; Yakovlev, Andrei A. (World Bank, Washington, DC, 2016)
This paper argues that although the bulk of the literature tends to focus on regulatory uncertainty stemming from formal practices, uncertainty that comes from unpredictable informal practices surrounding regulation is an underexplored additional form of regulatory uncertainty. The paper uses the results of empirical analysis of several unique firm-level data sets to argue that firms in Russian institutional environments adapt to informal practices of business-government interactions, so long as these practices are predictable. The paper draws a distinction between differences in levels of relatively well-ordered (and often centralized) and therefore predictable corruption—a predictable component of the cost of doing business—and variation in experiences with corruption, which often results from decentralized, unconstrained ("administrative") corruption and the rent-seeking incentives of lower level officials. It argues that a significant obstacle to investment decisions at the regional level is not so much formal or informal rules per se, but lack of predictability of their application. It also examines in-country inconsistency in property rights enforcement as another source of underexplored regulatory uncertainty tied to informal practice. Unlike administrative corruption, inconsistent property rights enforcement is a fundamental, existential threat to businesses. To test this hypothesis, the paper draws on a measure that captures private "raiders'" attacks on firms—hostile, often violent takeovers of firms by outsiders aided and often abetted by law enforcement agencies. The paper argues that the greater is the number of raider attacks for a given region, the greater is the uncertainty and the less likely is investment.